2003
DOI: 10.1557/jmr.2003.0302
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the electrokinetic behaviors of abrasive ceria particles and the deposited plasma-enhanced tetraethylorthosilicate and chemically vapor deposited Si3N4 films in an aqueous medium on chemical mechanical planarization for shallow trench isolation

Abstract: The effects of the electrokinetic behavior of abrasive ceria particles suspended in an aqueous medium and the deposited plasma-enhanced tetraethylorthosilicate (PETEOS) and chemical vapor deposition (CVD) Si3N4 films on chemical mechanical planarization (CMP) for shallow trench isolation were investigated. The colloidal characteristics of ceria slurries, such as their stability and surface potential, in acidic, neutral, and alkaline suspensions were examined to determine the correlation between the colloidal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 19 publications
0
21
1
1
Order By: Relevance
“…It is of interest that there was no significant difference of the surface forces between the tip and film, even in the presence of CMC, which indicated that as a result of the electrostatic repulsion between CMC and the Si wafer surface, CMC was only slightly adsorbed onto the Si wafer surface. At alkaline pH, the carboxylic acid of CMC is almost fully ionized and CMC has an extendedchain configuration [18]. Therefore, it was suggested that the formation of a hydro-plane on the Si wafer surface did not take place using the suspension prepared with CMC.…”
Section: Resultsmentioning
confidence: 99%
“…It is of interest that there was no significant difference of the surface forces between the tip and film, even in the presence of CMC, which indicated that as a result of the electrostatic repulsion between CMC and the Si wafer surface, CMC was only slightly adsorbed onto the Si wafer surface. At alkaline pH, the carboxylic acid of CMC is almost fully ionized and CMC has an extendedchain configuration [18]. Therefore, it was suggested that the formation of a hydro-plane on the Si wafer surface did not take place using the suspension prepared with CMC.…”
Section: Resultsmentioning
confidence: 99%
“…Ceria slurries are commonly stabilized by water soluble polymers such as poly methylacr ylate acid (PMMA) and poly acrylic acid (PAA) for dielectric CMP [26)]. The adsorption of these polymers is believed to increase the zeta potential of ceria abrasives in neutral and alkaline pH range from 6 to 9 [27)]. This increase in the zeta potential of ceria abrasives is understood to be due to ionization of the polymeric molecules to form negatively charged macromolecules with increase in pH of the solution.…”
Section: Stability Of Aqueous Ceria Dispersionsmentioning
confidence: 99%
“…This increase in the zeta potential of ceria abrasives is understood to be due to ionization of the polymeric molecules to form negatively charged macromolecules with increase in pH of the solution. Kim et al found that ceria slurries, containing 1 % abrasives and 1 % PMMA, were very well dispersed in neutral and alkaline conditions with narrow particle size distribution from 0.01 to 1 µm [27)]. By contrast, the same dispersion in acidic pH condition was observed to be unstable with a large agglomeration of particles and a wide size distribution ranging from 0.02 to 100 µm.…”
Section: Stability Of Aqueous Ceria Dispersionsmentioning
confidence: 99%
“…O óxido de cério é de grande importância por suas propriedades ópticas, alta estabilidade térmica, condutividade elétrica e difusividade, e a capacidade para armazenar e liberar oxigénio. Por estas propriedades, o CeO 2 pode ser utilizado como abrasivo [2], pigmento [3], material de catálise [4], eletrólito sólido de condução de íons oxigênio [5], e sensor de oxigênio [6]. Nos últimos anos foram realizadas algumas tentativas para a preparação de óxido de cério dopado com íons terras raras por várias técnicas, tais como pirólise [7], síntese solvotérmica [8,9], síntese sonoquímica [10], coprecipitação de dois estágios [11,12], processo sol-gel [13,14], reações de estado sólido [15], irradiação por micro-ondas [16], etc.…”
Section: Introductionunclassified